A Reappraisal of the Role of Abscisic Acid and its Interaction with Auxin in Apical Dominance - CLINE, MORRIS G. (Oxford University Press, 2006)
• Background and Aims Evidence from pea rms1, Arabidopsis max4 and petunia dad1 mutant studies suggest an unidentified carotenoid-derived/plastid-produced branching inhibitor which moves acropetally from the roots to the shoots and interacts with auxin in the control of apical dominance. Since the plant hormone, abscisic acid (ABA), known to inhibit some growth processes, is also carotenoid derived/plastid produced, and because there has been indirect evidence for its involvement with branching, a re-examination of the role of ABA in apical dominance is timely. Even though it has been determined that ABA probably is not the second messenger for auxin in apical dominance and is not the above-mentioned unidentified branching inhibitor, the similarity of their derivation suggests possible relationships and/or interactions. • Methods The classic Thimann–Skoog auxin replacement test for apical dominance with auxin [0·5 % naphthalene acetic acid (NAA)] applied both apically and basally was combined in similar treatments with 1 % ABA in Ipomoea nil (Japanese Morning Glory), Solanum lycopersicum (Better Boy tomato) and Helianthus annuus (Mammoth Grey-striped Sunflower). • Key Results Auxin, apically applied to the cut stem surface of decapitated shoots, strongly restored apical dominance in all three species, whereas the similar treatment with ABA did not. However, when ABA was applied basally, i.e. below the lateral bud of interest, there was a significant moderate repression of its outgrowth in Ipomoea and Solanum. There was also some additive repression when apical auxin and basal ABA treatments were combined in Ipomoea. • Conclusion The finding that basally applied ABA is able partially to restore apical dominance via acropetal transport up the shoot suggests possible interactions between ABA, auxin and the unidentified carotenoid-derived branching inhibitor that justify further investigation.